Analisis Pemahaman Sertifikasi Halal Pada Pelaku UMKM Ingkung di Kalurahan Guwosari - Hamidah Rayhanah; Nur Saudah Al Arifah D (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study aims to analyze the level of understanding of micro, small, and medium enterprise (MSME) actors in the ingkung culinary sector toward halal certification in Guwosari Village, Pajangan District, Bantul Regency, Special Region of Yogyakarta. Indonesia, as the country with the largest Muslim population in the world, holds strategic importance in the global halal industry. However, data from the Halal Product Guarantee Agency (BPJPH) indicates that as of 2024, only approximately 12.35% of registered MSMEs in Indonesia have obtained halal certification — a figure that reflects a significant implementation gap. This research employs a mixed methods approach with an explanatory sequential design, integrating quantitative and qualitative data. Quantitative data were collected via questionnaire distributed to 13 MSME actors selected through total sampling, while qualitative data were gathered through in-depth interviews to corroborate the quantitative findings. Data analysis employed descriptive statistics, validity testing, reliability testing, Spearman rank correlation analysis, and the interactive model of Miles and Huberman. The Spearman correlation analysis revealed a significant positive relationship between respondents’ level of understanding (conceptual and technical), motivation, and perception of benefits with their readiness to implement halal certification. Findings indicate that MSME actors possess a high level of conceptual understanding of halal certification, particularly concerning product halalness, consumer trust, and business competitiveness. However, understanding of technical and administrative aspects remains low. This study identifies a conceptual-implementation gap: although motivation and perception of benefits are high, actual implementation remains minimal due to limited information access, low digital literacy, perceived procedural complexity, and insufficient technical assistance. The novelty of this research lies in its analysis of the implementation gap within traditional culinary MSMEs at the sub-district level — a context underexplored in prior literature that typically focuses on urban or district-level MSMEs. These findings are expected to inform policy strategies for halal certification education and technical assistance programs targeting traditional MSME actors.